From Russia with doubt : the quest to authenticate 181 would-be masterpieces of the Russian avant-garde - Lerner, Adam (Princeton Architectural Press, 2014)
"In 2010 the Museum of Contemporary Art Denver director Adam Lerner did something unheard of in the museum world: he mounted a large exhibition of paintings without first knowing whether they were real or fakes. Painted in the Suprematist and Constructivist style of early twentieth-century Russian avant-garde masters, the 181 canvases had been acquired by amateur collectors Ron and Roger Pollard from a mysterious seller in Germany they met on eBay who claimed the paintings were found in an abandoned shipping container held in German customs since the 1980s. In From Russia with Doubt, Lerner skillfully weaves together the tale--from the initial eBay find to his controversial decision to exhibit the collection--guiding readers through the looking glass into the Byzantine corridors of the art world and beyond, describing the owners' quest to authenticate and appraise the would-be masterpieces. What he finds raises powerful questions about our own relationship to art"--